Gladiolus hybridus ABSCISIC ACID INSENSITIVE 5 (GhABI5) is an important transcription factor in ABA signaling that can enhance Gladiolus corm dormancy and Arabidopsis seed dormancy. - Wu, Jian; Seng, Shanshan; Sui, Juanjuan; Vonapartis, Eliana; Luo, Xian; Gong, Benhe; Liu, Chen; Wu, Chenyu; Liu, Chao; Zhang, Fengqin; He, Junna; Yi, Mingfang (Frontiers in Plant Science, 2015)
The phytohormone abscisic acid (ABA) regulates plant development and is crucial for abiotic stress response. In this study, cold storage contributes to reducing endogenous ABA content, resulting in dormancy breaking of Gladiolus. The ABA inhibitor fluridone also promotes germination, suggesting that ABA is an important hormone that regulates corm dormancy. Here, we report the identification and functional characterization of the Gladiolus ABI5 homolog (GhABI5), which is a basic leucine zipper motif transcriptional factor (TF). GhABI5 is expressed in dormant vegetative organs (corm, cormel and stolon) as well as in reproductive organs (stamen), and it is up-regulated by ABA or drought. Complementation analysis reveals that GhABI5 rescues the ABA insensitivity of abi5-3 during seed germination and induces the expression of downstream ABA response genes in Arabidopsis thaliana (EM1, EM6 and RD29B). Down-regulation of GhABI5 in dormant cormels via Virus Induced Gene Silence (VIGS) promotes sprouting and reduces the expression of downstream genes (GhLEA and GhRD29B). The results of this study reveal that GhABI5 regulates bud dormancy (vegetative organ) in Gladiolus in addition to its well-studied function in Arabidopsis seeds (reproductive organ).